ABOUT SOME THERMOPHYSICS PROPERTIES OF “LIQUID-GAS” CONNECTING ZONE - Ermekov, М.М.; Еrmekov, Sh. K.; Ibrashev, K.N. (Recent Contributions to Physics, 2021)
Analytical calculations are organized in work with provision for experimental installed and reference importances physico-chemical parameter, participating in forming the connecting zone under mixing mode of the displacing to hydrocarbon liquid dissolved friend in friend by gas with her.